PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK MELALUI PEMBERIAN REWARD STICKER PADA PEMBELAJARAN FISIKA - Widya Bratha Sheftyawan; Febrianti Utami; U'ud Efendi; Bambang Supriadi (Universitas Jember, 2023)
The purpose of this research was to analyze whether attaching a reward sticker in a physics class increases motivation for learning. This research uses the quantitative descriptive method. The type of study is classroom action research in two phases, cycle 1 and cycle 2. The study subjects were up to 34 students from class X4 SMAN 5 Jember. Data collection techniques using Google forms, observations, questionnaires packaged in documents. Data analysis techniques using quantitative descriptive analysis. The study showed a 9% increase in the highly motivated category and a 76% increase in the very motivated category. The conclusion of this study was that rewarding stickers can increase students' motivation to learn during the learning process.